Pasting properties mixtures of mangrove fruit flour (Sonneratia caseolaris) and starches - Estiasih, T. (2016)
Mangrove fruit from species Sonneratia caseolaris can be an important raw material in functional food with dietary fiber, vitamins, and flavonoid, as well as its anti-cholesterol and anti-diabetic properties. Understanding its pasting properties of the flour from it when mixed with starches will further enhance its utilization as a functional ingredient, so its can be added to food as a supplement to enhance the beneficial health properties.The aims of this research were to study pasting properties, including physicochemical. An experiment the mangrove fruit flour (Mang) mixed with waxy maize starch (WaMa), potato starch (PS) and wheat flour (WhF) at level ranges of 0-100% were studied in water using the Rapid Visco-Analyser (RVA). The results showed that the mangrove fruit flour did not change the pasting patterns of the mixtures, and the pasting temperatures of the samples ranged 65.1–77.3oC. The mangrove fruit flour significantly decreased (p < 0.05) the pasting parameters of the WaMa and PS as it diluted the starch contents in the mixtures. The peak viscosity of the Mang:WaMa mixtures decreased from 4342 to 1617cP. Similarly, in the Mang:PS it decreased from 10883 to 3127cP and in the Mang:WhF from 4079 to 1651 cP. The mangrove fruit flour did not change the setback viscosity of the Mang:PS and Mang:WhF mixtures, and there were significant positive correlations (r ≥ 0.89; p ≤ 0.01) between the breakdown and peak viscosities of the mixtures. In mangrove fruit composite flours, therefore, more starch-containing base flours are required to achieve the same consistency as the undiluted flours.